Robust road condition detection system using in vehicle standard sensors. - Castillo-Aguilar, Juan Jesús; Cabrera-Carrillo, Juan Antonio; Guerra-Fernández, Antonio Jesús; Carabias-Acosta, Enrique (MDPI, 2015)
The appearance of active safety systems, such as Anti-lock Braking System, Traction Control System, Stability Control System, etc., represents a major evolution in road safety. In the automotive sector, the term vehicle active safety systems refers to those whose goal is to help avoid a crash or to reduce the risk of having an accident. These systems safeguard us, being in continuous evolution and incorporating new capabilities continuously. In order for these systems and vehicles to work adequately, they need to know some fundamental information: the road condition on which the vehicle is circulating. This early road detection is intended to allow vehicle control systems to act faster and more suitably, thus obtaining a substantial advantage. In this work, we try to detect the road condition the vehicle is being driven on, using the standard sensors installed in commercial vehicles. Vehicle models were programmed in on-board systems to perform real-time estimations of the forces of contact between the wheel and road and the speed of the vehicle. Subsequently, a fuzzy logic block is used to obtain an index representing the road condition. Finally, an artificial neural network was used to provide the optimal slip for each surface. Simulations and experiments verified the proposed method.
Keywords: Vehículos de motor - Dispositivos de seguridad; Ingeniería - Aparatos e instrumentos; Fricción superficial (Aerodinámica); Deslizamiento (Mecánica); Standard vehicle sensor; Friction estimation; Optimal slip estimation; Normal driving